Photo-healable ion gel with high mechanical property, fatigue resistance and shear resistance using a coumarin group containing diblock copolymer in an ionic liquid. (15th February 2022) - Wang, Lei; Chen, Jing; Sha, Ye; Hussain, Imtiaz; Yu, Bo; Wu, Linlin; Shi, Yijun; Gu, Qun; Luo, Zhenyang; Ma, Xiaofeng
Graphical abstract: Highlights: Coumarin containing random copolymers MM and diblock copolymer SMM are prepared. SMM ion gel shows higher mechanical property, fatigue resistance and shear resistance than MM ion gel. MM and SMM in ionic liquid show photo-induced reversible sol–gel and jammed micelle-gel transition. SMM ion gel shows high photo-healing efficiency compared to MM ion gel. The electrochemical properties of SMM ion gel can be recovered completely after photo-healing process. Abstract: Ion gels, polymer networks swollen with ionic liquid (IL), are ideal materials for application in flexible electronic devices. It remains a challenge to fabricate an ion gel with photo-healing, high mechanical properties, fatigue resistance and shear resistance. Herein, a well-defined diblock copolymer polystyrene- b -poly(methyl acrylate- r -7-(2′-methacryloyloyloxyethoxy)-4-methylcoumarin) (PS- b -P(DMA- r -MAOEMC), brief name: SMM, PS: IL-phobic segment and P(DMA- r -MAOEMC): IL-philic segment) was synthesized by reversible addition fragmentation chain transfer (RAFT) polymerization. For comparison, a random copolymer P(DMA- r -MAOEMC) (MM) also be prepared. In dilute solution, the SMM can form spherical micelles with PS-core surrounded by P(DMA- r -MAOEMC) corona chains in an IL, 1-ethyl-3-methylimidazolium bis(trifluoromethane sulfone)amide ([C2 mim][NTf2 ]). In a suitable polymer concentration, the SMM and MM can form ion gels in [C2 mim][NTf2 ] under 365 nm UV light irradiation through photo-dimerization of coumarin groups in corona MM polymer chains of spherical micelles and photo-dimerization of coumarin groups in MM random polymer chains, respectively. Compared with the MM ion gel, the SMM ion gel has high mechanical properties, shear resistance and relatively high fatigue resistance. Under 254 nm UV light irradiation, photo-induced gel to jammed micelles transition for the SMM ion gel and photo-induced gel to sol transition for the MM ion gel occur due to photo-cleavage of dimer in polymer chains. Photo-induced jammed micelles - gel transition for the SMM ion gel and photo-induced sol - gel transition for the MM ion gel are reversible by alternating 365 nm and 254 nm UV light irradiation, whereby photo-healable materials can be fabricated. Compared to the MM ion gel, the SMM ion gel has high photo-healing efficiency. The electrochemical property of the SMM ion gel can be recovered completely after photo-healing.